Optimal reactive power planning using two-stage stochastic chance-constrained programming - Lopez, Julio C. [UNESP]; Mantovani, J. R.S. [UNESP]; Sanz, Javier Contreras; Munoz, Jose I. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
In this paper, the optimal reactive power planning considering uncertainty is presented. The classical deterministic mixed-integer nonlinear model is expanded into two-stage stochastic model with chance-constraint. This new model considers uncertainty on the demand and the equivalent availability of the reactive power sources. The concepts of expected value of perfect information (EVPI) and the value of the stochastic solution (VSS) are also studied. Finally the proposed model is applied to IEEE 30-bus test system to determine optimal amount and location for reactive power expansion. © 2013 IEEE.
Keywords: Chance-constraint; optimal reactive power planning; stochastic programming; uncertainty